From Text to Work: Digital Tools and the Emergence of the Social Text - McGann, Jerome (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractThe essay is a study of how critical editions work, whether in paper-based forms or in electronic forms. The first section – more than half the essay – gives a close examination to J. C. C. Mays’s superb recent (Bollingen) edition of Coleridge’s poetry. This analysis establishes the terms for investigating the opportunities that digital technology supplies for scholars pursuing a close study of the socio-historical character of literary works. This investigation pivots around the seminal work of D. F. McKenzie, whose theory of the social-text edition argues for a more comprehensive kind of editorial method. This essay argues that the method can be best realized through digital resources. It concludes with a discussion of The Rossetti Archive as a “proof of concept” experiment to test the social-text approach to editorial method.